Food safety attitudes, beliefs, knowledge and self-reported practices of college students before and after educational intervention - Yarrow, Linda K. (Kansas State University, 2006)
Preventing foodborne illness and promoting safe food practices among all age groups is a high priority, particularly for college students because little about their food safety awareness and food handling practices has been reported. The research aim was to evaluate food safety attitudes, beliefs, knowledge, and self-reported practices of current upper-division college students, and to determine whether a three-module interactive educational intervention, developed for this study, positively influenced these variables. Comparisons between health and non-health majors were made. Two methods of data collection were used with volunteer health and non-health majors: focused food safety discussion groups during academic year 2004-05, and a pre-experimental design. Prior to engaging in either method, students completed an on-line food safety questionnaire (FSQ), adapted from a telephone survey used at K-State with older adults. The FSQ was administered again to those in the pre-experimental design group one week after exposure to the food safety educational intervention. Five weeks later, the FSQ was administered to determine whether changes in attitudes, beliefs, knowledge, and self-reported practices persisted over time. Focused food safety discussion group responses were qualitatively evaluated. Pre-experimental statistical analyses included Wilcoxin Signed Rank, Friedman, Mann-Whitney U, Chi Square tests, and Spearman rho. Focused discussion group findings indicated that students perceived themselves at low risk for foodborne illness; few used food thermometers; students without health backgrounds mimicked undesirable home practices; and students stated being open to changing non-recommended behaviors. Pre-experimental findings showed the effects of intervention were improved food safety attitudes, beliefs, and knowledge, with the strongest effects seen in health majors. Students' FSQ attitude scores increased from 114 to 122 (P<0.001), FSQ belief scores increased from 86 to 98 (P<0.001), and FSQ knowledge scores increased from 11 to 13 (P<0.001). Intervention resulted in some improved food safety self-reported practices for health majors but not non-health majors. Intervention module post-test scores improved significantly for all students; health majors had greater increases. Conclusions. Focused food safety discussion groups were useful for obtaining food safety information from college students; educational intervention improved college studentsâ food safety attitudes, beliefs, and knowledge and for health majors, some self-reported practices improved.
Keywords: Food safety; Food safety education; College student education; Food safety attitudes; Food safety beliefs; Food safety knowledge; Health Sciences, Education (0350); Health Sciences, Nutrition (0570)